Altitude and Distance Relationships with the Multidimensional Poverty Index: The case of Peru - Delgado, Augusto (2023)
This paper studies the potential association between two geographic indicators, distance and altitude, with the Multidimensional Poverty Index (MPI) for 1,874 district in Peru by using the National Census of 2017. We investigate whether higher altitude or longer distance is associated with higher MPI values. For this purpose, we use the distance of each district to three different potential spaces of reference. First, we use the shortest distance to the metropolitan area of Lima; second, the shortest distance to the capitals of coastal departments; third, and finally, the shortest distance to the sea. We obtain three relevant results. First, we find evidence that altitude is statistically significant and positive associated with variation of MPI among districts. Second, the distance with respect to the sea appears to be more relevant to explaining differences in MPI than the distance to the Metropolitan area or coastal departmental capitals. Finally, we find evidence of spatial externalities of MPI across districts which also seem to be stronger than the direct effect of altitude and distance.